2010
DOI: 10.1002/ejoc.201000477
|View full text |Cite
|
Sign up to set email alerts
|

Practical Synthetic Approach to Chiral Sulfonimides (CSIs) – Chiral Brønsted Acids for Organocatalysis

Abstract: A general approach to the synthesis of optically pure 3,3Ј-diaryl chiral sulfonimides (CSIs) from racemic BINOL has been developed. ortho-Lithiation is directed by the sulfonyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 33 publications
3
24
0
1
Order By: Relevance
“…Remarkably, in 2010, Lee and co-workers developed a practical synthesis of (R)-3,3'-diaryl-1,1'-binaphthyl-2,2'-disulfonimides ((R)-24) from the parent (R)-3,3'-dibromo compound (R)-32 by Suzuki-Miyaura coupling with ArB(OH) 2 (Scheme 10). [16] The (R)-3,3'-diiodo compound was also synthesized and used as a common precursor through the coupling reaction. Their synthetic method is valuable, as the aryl moiety with both electron-donating and electron-withdrawing groups can be introduced at the 3,3'-positions of the binaphthyl structure in good to high yields.…”
Section: Synthesis Of Optically Pure 33'-diaryl-binsasmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, in 2010, Lee and co-workers developed a practical synthesis of (R)-3,3'-diaryl-1,1'-binaphthyl-2,2'-disulfonimides ((R)-24) from the parent (R)-3,3'-dibromo compound (R)-32 by Suzuki-Miyaura coupling with ArB(OH) 2 (Scheme 10). [16] The (R)-3,3'-diiodo compound was also synthesized and used as a common precursor through the coupling reaction. Their synthetic method is valuable, as the aryl moiety with both electron-donating and electron-withdrawing groups can be introduced at the 3,3'-positions of the binaphthyl structure in good to high yields.…”
Section: Synthesis Of Optically Pure 33'-diaryl-binsasmentioning
confidence: 99%
“…To apply this stepwise reduction and oxidation method to the synthesis of chiral 3,3'-Ar 2 -BINSA (22), Ishihara and co-workers used N-Me disulfonimide (S)-33 as a common intermediate after the N-methylation of (S)-32 [16] in the initial step (Scheme 11). A suitable aryl moiety was then introduced at the 3,3'-positions of the binaphthyl skeleton, followed by cleavage of the first N À S bond of disulfonimide (S)-34 with the use of NaOH in MeOH (2 m) at reflux, protection of the SO 3 Na moiety with Et 3 O·BF 4 , and protection of the SO 2 NHMe moiety with Me 3 O·BF 4 .…”
Section: Synthesis Of Optically Pure 33'-diaryl-binsasmentioning
confidence: 99%
“…Rev. XXXX, XXX, XXX−XXX N synthetic route to 3,3′-substituted binaphthyl disulfonimides based on the late-stage ortho-lithiation 187. Introduction of a halogen (Br or I) followed by the Suzuki−Miyaura crosscoupling reaction afforded desired binaphthyl disulfonimides 4 in acceptable chemical yields (over 70%) (Scheme 64).An effective method for cleavage of the N−S bond is required to produce BINSA derivatives from 3…”
mentioning
confidence: 98%
“…Along these lines, the in situ lithiation/halogenation of the unsubstituted disulfonimide was reported by Lee et al, enabling convenient and efficient late-stage Suzuki couplings. [21] Apart from this particular study, the concept of lithiation by means of directed ortho-metalation (DoM) followed by alkylation for the synthesis of new chiral organocatalysts was not further examined, although the orthodirecting properties of, for example, SO 2 NR 2 and P(O)(tBu) 2 groups are well known. [22] We found that (biaryl)hydroxyl acids (HYDRAs) can be synthesized directly from the corresponding unsubstituted disulfonimides.…”
mentioning
confidence: 99%